Determination of parabens and bisphenol A in sludge samples using hydrophobic deep eutectic solvents by gas chromatography coupled to mass spectrometry and sample introduction via pyrolizer - Ferreira, Karen Chibana [UNESP]; Rodrigues, Thais [UNESP]; Isquibola, Guilherme [UNESP]; Ayala-Durán, Saidy Cristina [UNESP]; Merib, Josias de Oliveira; Gonzalez, Mario H. [UNESP]; Anderson, Jared L.; de Lima Gomes, Paulo Clairmont F. [UNESP] (Elsevier, 2024)
This study reports on the development and use of hydrophobic deep eutectic solvents (HDES) as environmentally-friendly solvents to address the demand for low-toxicity materials for analysts and the environment. The study involved the application of HDES in environmental matrices for extracting emerging contaminants. In this case, HDESs were used as extraction solvents in dispersive liquid–liquid microextraction (DLLME) to determine parabens and bisphenol A from sludge samples. Gas chromatography-mass spectrometry (GC–MS) featuring a pyrolizer was used for sample introduction. Chemometric tools were utilized to optimize analysis conditions, considering the sample introduction and DLLME parameters. HDESs were characterized using Fourier-Transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and thermogravimetric analysis (TG). Univariate and multivariate strategies were employed to determine the optimal experimental conditions. In this case, the injection volume was fixed as 20 µL, with a temperature of 320 °C and a pyrolizer duration time of 0.5 min. For DLLME, full factorial design permitted identification of the best condition of each experimental variable, including the salting-out effect, pH, volume of dispersing solvent, and volume of extraction solvent. Optimal conditions for DLLME in sludge samples were determined as 300 µL of HDES, 350 µL of ACN, pH = 10, and the addition of NaCl at 27% m/v. Following optimization studies, a HDES was successfully applied as an extraction solvent to determine endocrine disruptors in sludge samples. Future work involves the analysis of additional sludge samples (both liquid and solid phases) using standard addition to quantify analytes using the developed methodology. The utilization of HDES within environmental samples facilitated the identification of emerging contaminants, aligning with the tenets of sustainable analytical chemistry. This was substantiated by applying the GREEnness Analytical (AGREE) evaluation metric system, yielding values of 0.72 and 0.76 for the employed methodology and sample preparation, respectively.
Keywords: Gas chromatography; Hydrophobic deep eutectic solvents; Pyrolizer; Sample preparation